PEMANFAATAN TEKNOLOGI PEMBUATAN POC GUNA MENAMBAH KETERAMPILAN DAN PENGHASILAN TAMBAHAN RUMAH TANGGA DI DESA UTEUNKOT LHOKSEUMAWE - Halus Satriawan; Laila Nazirah (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Realizing a commitment to food security is closely related to social security, economic stability, political stability and national security or resilience. Continuous improvement of fertile land through the use of liquid organic fertilizers is expected to maintain the quality of soil nutrients which in turn will improve the quality of agriculture and the productivity of food crops. Based on observations in the field, the people of Uteunkot Village, Lhokseumawe City, had not managed waste properly, organic and inorganic waste had not been separated from one another, and waste was often thrown away without proper handling, causing foul odor that disturbs the environment. To overcome this problem, a solution was needed, namely utilizing organic waste as liquid organic fertilizer which is useful for the community in fertilizing plants in the yard of the house. This community service was held from July to September 2022 in Uteunkot Village, Lhokseumawe City. The purpose of this service activity was to find out the impact of counseling on the community regarding the manufacture and use of liquid organic fertilizer. The results of the community service activities showed the compatibility between the implementation and the guidelines for making liquid organic fertilizer from household organic waste, as well as increasing the knowledge of farmer groups in Uteunkot Village, Lhokseumawe City.